DEMOGRAPHIC GROWTH AND ITS INFLUENCE ON THE SOCIOECONOMIC DEVELOPMENT OF UZBEKISTAN - Malika Saidmurodova (Scholar Express Journal, 2025)
This article is dedicated to the analysis of demographic development in Uzbekistan and its impact on the country’s socio-economic life. The study examines key demographic theories, such as Malthusian theory, the theory of demographic transition, Marxist theory, and the theory of sustainable development, which assist in analyzing and forecasting demographic changes. The demographic situation in Uzbekistan is analyzed, including trends in birth rates, death rates, natural population growth, age and gender structure, as well as migration processes. Special attention is given to the importance of migration policy, urbanization, and healthcare development in maintaining a stable demographic balance. Socio-economic factors influencing demographic processes, such as education levels, economic development, and cultural changes, are also considered. The article provides forecasts of Uzbekistan’s demographic growth and its impact on socio-economic development, emphasizing the need for a comprehensive state policy to address demographic challenges, ensure sustainable growth, and improve the quality of life for the population.
Keywords: Demographic development; socio-economic life; Uzbekistan